Improvement of bioavailability of bioactive compounds of medicinal herbs by drying and fermentation with Lactobacillus plantarum - Dogan, Kubra; Tornuk, Fatih (FUNCTIONAL FOOD CENTER INC, 2019)
Background: Medicinal and aromatic plants, which are rich sources of bioactive conpounds, have been used in traditional medicine for ancient times. Epidemiological studies have shown that bioactive compounds of medicinal plants possess antioxidant, anti-inflammatory, antiatherosclerotic, antitumor, antimutagenic, anticarcinogenic, antibacterial and antiviral activities. Intake of natural antioxidants derived from medicinal plants into body has been associated with reduced risks of cancer, cardiovascular disease, diabetes, and other diseases. It has also been demonstrated that the fermentation of plants is a versatile way for improvement of their functionality and bioavailability. The aim of this study was to determine the effect of probiotic fermentation and vacuum drying on the bioavailability of peppermint (Mentha piperita) and basil (Ocimum basilicum) exposed to in vitro digestion. Methods: Fresh basil and peppermint were divided to 3 lots, one lot of each plant was vacuum dried at 40 degrees C for 8 hours to obtain the dried samples while one lot was fermented with probiotic Lactobacillus plantarum for 21 days at room temperature after incorporation with sterile brine (1:20 w:v) containing 5 % of NaCl. Thereby, 3 samples were obtained: Fresh peppermint/basil, vacuum dried peppermint/basil and fermented peppermint/basil. During the in vitro digestion comprised from gastric and pancreatic digestion, bioavailability of the samples were investigated by measurement of their total phenolic contents (TPCs), total flavonoid contents (TFCs) and antiradical activity. TPC was determined using Folin-Ciocalteu method while TFC was measured aluminum chloride colorimetric assay. The antiradical activity of the samples was analyzed by determination of the DPPH radical scavenging activity. Results: The initial (undigested) TPC levels of fresh, vacuum dried and fermented mint and basils ranged from 166.24 to 295.08 mg gallic acid equivalent (GAE)/g. Drying and fermentation increased TPCs of the plants. Similarly, TFCs and antiradical activities were also increased by these treatments. When considering bioavailability of the bioactive compounds, fermentation process enabled higher recovery levels after in vitro digestion while basil exhibited higher percent recovery than mint. Conclusion: This study demonstrated that vacuum drying and fermentation of basil and mint with probiotic Lactobacillus plantarum provided much stronger antioxidant activity and bioavailability than fresh ones and increased their in vitro bioavailability.
Keywords: IN-VITRO DIGESTION; TOTAL PHENOLIC CONTENT; ANTIOXIDANT ACTIVITY; OCIMUM-BASILICUM; SWEET BASIL; CAPACITY; EXTRACTS; FOODS; L.; Food Science & Technology